A contribution to marxist memory studies - Kirn, Gal (Družboslovne razprave, 2025)
The text departs from Traverso’s hypothesis concerning the impossibility of Marxism and Memory Studies encountering each other, and juxtaposes it with a few theoretical areas in Marx that may be useful for contributing to Marxist Memory Studies. The dialectical relationship within capitalism between the structurally necessary forgetting of violence and the structural remembering of debt is described before the concept of the primitive accumulation of capital and Lazzarato’s (2013) crucial notion of indebted subjectivity is deployed. The moral and memorial aspects of debt have been often overlooked by Marxism, while the relationship of memory to debt and capital has been completely ignored by the majority of memory-studies scholars. In the conclusion, it is argued that this missing link provides fertile grounds for Marxist Memory Studies and for furthering debates, especially on the topics of reparation, restitution, and debt cancellation.
Keywords: absence of violence; cancellation of debt; Enzo Traverso; indebted subject; marksistične spominske študije; marxist memory studies; memory economy; odpis dolgov; odsotnost nasilja; primitive accumulation of memory; primitivna akumulacija spomina; remembrance of debt; spominjanje dolga; spominska ekonomija; zadolžena subjektivnost